2010
DOI: 10.1029/2010jc006500
|View full text |Cite
|
Sign up to set email alerts
|

Global correlations between winds and ocean chlorophyll

Abstract: [1] Global time series of satellite-derived winds and surface chlorophyll concentration (Chl-a) show patterns of coherent areas with either positive or negative correlations. The correlation between Chl-a and wind speed is generally negative in areas with deep mixed layers and positive in areas with shallow mixed layers. These patterns are interpreted in terms of the main limiting factors that control phytoplankton growth, i.e., either nutrients that control phytoplankton biomass in areas with positive correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 39 publications
7
67
1
Order By: Relevance
“…Here, the direct effects of increasing temperature have been hypothesized to result in an earlier onset of the spring bloom (e.g., Sverdrup, 1953;Lewandowska and Sommer, 2010) and hence a longer production season (Kahru et al, 2010;Dalpadado et al, 2014). In regions with seasonal variations in sea-ice cover, higher temperatures reduce sea-ice extent which also results in earlier blooms, a longer growing season and increased area available for production, thus resulting in higher productivity (Mueter et al, 2009;Kahru et al, 2011;Dalpadado et al, 2014).…”
Section: Phytoplankton Productionmentioning
confidence: 99%
“…Here, the direct effects of increasing temperature have been hypothesized to result in an earlier onset of the spring bloom (e.g., Sverdrup, 1953;Lewandowska and Sommer, 2010) and hence a longer production season (Kahru et al, 2010;Dalpadado et al, 2014). In regions with seasonal variations in sea-ice cover, higher temperatures reduce sea-ice extent which also results in earlier blooms, a longer growing season and increased area available for production, thus resulting in higher productivity (Mueter et al, 2009;Kahru et al, 2011;Dalpadado et al, 2014).…”
Section: Phytoplankton Productionmentioning
confidence: 99%
“…However, large uncertainties remain in observed and anticipated responses in the biology and biogeochemistry of the Arctic Ocean (e.g., Grebmeier et al, 2010;Wassmann et al, 2011). For example, increased ice-free area and warmer temperatures may have caused changes in rates of primary production in the deep Arctic (e.g., Arrigo et al, 2008Arrigo et al, , 2014Arrigo and van Dijken, 2011) and associated shelves (e.g., Ardyna et al, 2014), timing of the annual phytoplankton bloom (e.g., Kahru et al, 2010), composition of phytoplankton (e.g., Li et al, 2009), and functioning of the biological ABSTRACT. The Russian-American Long-term Census of the Arctic (RUSALCA) project provides a rare opportunity to study the Russian sector of the Pacific Arctic Region (PAR), which includes the Chukchi and East Siberian Seas.…”
Section: Introductionmentioning
confidence: 99%
“…In the tropics and subtropics, zonal wind stress patterns cause convergence zones and increase sea level (Palanisamy et al 2015). Such zones are also characterized by deep thermoclines and low nutrient availability, which are unfavourable for phytoplankton production (Kahru et al 2010); a negative correlation between SSH and chlorophyll concentration can be observed (Turk et al 2001). In high latitudes, oceanic convergence zones also show an increase in SSH, but the conditions may still favour phytoplankton production due to enhanced upper ocean light availability and supply of nutrients from winter mixing.…”
Section: General Principlesmentioning
confidence: 99%